Profil Computational Thinking Skill Siswa SMP dalam Pembelajaran IPA - Izzah, Nuril Ayyamil; Suwaibatulilla, Anggun; Khasfiyatin, Siti; Jayati, Rina Tut; Supeno, Supeno (Universitas Pendidikan Mandalika, 2023)
This research aims to describe the profile of students' computational thinking skills (CTS) in solving problems on topics about work, energy, and simple machines in science learning. This research was conducted using a descriptive method with a quantitative approach. The subjects in this research were students in classes VIII A and IX A of SMP Negeri 4 Jember for the 2023/2024 academic year, with a total of 64 students from each class taken from 32 students in each class. The data collection technique in this research used a Computational Thinking essay test with 5 questions, which were then analyzed using quantitative descriptive analysis. Based on the research results, it is known that the CTS level of class VIII students was 35.97, so it was categorized as low, and the CTS level of class IX students was 53.59, which has been given treatment, so it is categorized as medium. The highest level that class VIII students could achieve was 55.47%, namely decomposition ability, and the lowest percentage was 2.18%, namely evaluation ability. Meanwhile, the highest level that could be achieved by class IX students who had received learning material on work, energy, and simple machines was 59.37%, namely decomposition ability, and the lowest level was 20.93%, namely pattern recognition ability.